1939
DOI: 10.2307/1436898
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Sea Fishes of the Bermuda Oceanographic Expeditions. Family Melanostomiatidae

Abstract: Genus Bathophilus Giglioli 196 B. brevis Regan & Trewavas 199 B. altipinnis Beebe 203 B. metallicus (Welsh) 205 B. longipinnis (Pappenheim) 208 B. chironema Regan & Trewavas 209 Genus Eustomias Vaillant 210 E. obscurus Vaillant 217 E. bibulbosus Parr 219 E. simplex Regan & Trewavas 221 E. dubius Parr 222 E. lipochirus Regan & Trewavas 224 E. bigelowi Welsh 225 E. silvescens Regan & Trewavas 228 E. schmidti Regan & Trewavas 230 E. fissibarbis Pappenheim 232 IV. Bibliography 233 Introduction.For detailed data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Within these subgenera, most of the species are distinguished by the structure and proportion of their barbels, whereas other morphologic and meristic values rarely are able to differentiate the species. Prior to Beebe & Crane (1939), most species were known from type specimens, lack any additional records, and almost every variation in features of the barbels was considered a separate species. Beebe & Crane (1939), based on only a few more specimens of certain forms, concluded that many differences in barbel structure were either sexual or ontogenetic variations, and reassigned several earlier forms to synonymies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these subgenera, most of the species are distinguished by the structure and proportion of their barbels, whereas other morphologic and meristic values rarely are able to differentiate the species. Prior to Beebe & Crane (1939), most species were known from type specimens, lack any additional records, and almost every variation in features of the barbels was considered a separate species. Beebe & Crane (1939), based on only a few more specimens of certain forms, concluded that many differences in barbel structure were either sexual or ontogenetic variations, and reassigned several earlier forms to synonymies.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to Beebe & Crane (1939), most species were known from type specimens, lack any additional records, and almost every variation in features of the barbels was considered a separate species. Beebe & Crane (1939), based on only a few more specimens of certain forms, concluded that many differences in barbel structure were either sexual or ontogenetic variations, and reassigned several earlier forms to synonymies. This concept was accepted and followed by Morrow & Gibbs (1964), which was based on rather few additional specimens.…”
Section: Introductionmentioning
confidence: 99%